An Elementary Proof of the Brouwer Fixed Point Theorem: Sompong Dhompongsa, Poom Kumam - Team, Support (Thai Journal of Mathematics, 2019)
A new proof of the Brouwer fixed point theorem is given. The proof does not depend on deep known results and it is self-contained.